KUMAN DAN UJI KEPEKAAN ANTIBIOTIK DI KAKI DIABETIK - Ari Sutjahjo (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2013)
The purpose of this study was to know the bacterial pattern causing foot infections in diabetes mellitus (DM) patients and the sensitivity test results of the bacteria against various antibiotics that have been set. This research was conducted as a retrospective study using medical records. The study was carried out on diabetic foot patients of all In-patient Wards, Department of Internal Medicine, Dr. Soetomo Hospital, who met the inclusion criteria between January 1, 2003 up to December 31, 2007. The stages were classified according to the Wagner - Merrit criteria. Laboratory and clinical data were taken from the medical records of the patients who were admitted. Infected diabetic foot was found in 30.9% of patients. The causative bacteria consisted of: Pseudomonas (20.3%), Streptococcus (15.25), Klebsiella (13.9%), E.coli (12.6%), Proteus (12.6%), and Staphylococcus (11.3%). The Imipenem antibiotic showed the highest sensitivity (99.2%), followed by Norfloxacin (98.8%), Meropenem (98.2%), Ofloxacin (97.7%) and Cefuroxime (95.3). In this study, it was found that the most resistancy was to Erythromycin (46.3%) followed by Chloramphenicol (44.2%), Ceftazidime (41.1%), Cefotaxime (36.6%) and Ciprofloxacin (33.5%). It can be concluded that most of the bacteria causing the diabetic foot infections were Gram-negative aerobic bacterias and the highest sensitivity was to Imipenem, Norfloxacin, Meropenem as well as Cefuroxime.